Hypnotic Effect of Salvia reuterana Boiss for Treatment of Insomnia - G Vaseghi; S Andalib; M Rabbani; SE Sajjadi; A Jafarian (Institue of Medicinal Plants, ACECR, 2013)
Background: Insomnia, which is difficulty in initiating and maintaining sleep, is a very common experience for many people. Considering the increasing interest in medicinal plants in the past decade, many plants such as Coriandrum sativum, Salvia leriifolia, Salvia reuterana and Stachys lavanduli folia have been used in Iranian traditional medicine to abate insomnia. Objective: The present study was designed to investigate hypnotic effect of Salvia reuterana on male mice. Methods: Ethanolic extract of S. reuterana was prepared. Five groups of 6 animals each were pretreated with vehicle, Salvia extract (50, 100 and 250 mg/kg i.p.) or diazepam (0.5mg/kg i.p.) 30 minutes before ketamine injection (100 mg/kg, i.p.). Results: The latency and total sleeping times were recorded to determine the hypnotic effect of the extract. The results indicated that ethanolic extract of S. reuterana, reduced the latency time and induced the total sleeping time in a dose dependent manner, compared to saline group. Conclusion: The present study suggests that S. reuterana produces hypnotic effect which can be evaluated clinically.